Green Nanotechnology for Biofuel Production (Biofuel and Biorefinery Technologies,, 2018)
This book focuses on the use of nanotechnology and nanomaterials in the production of biofuels. It describes the current production technologies for different biofuels and their limitations for commercialization, and discusses in detail how nanomaterials could reduce biofuel production costs. After an introduction to biofuels, the book examines biofuels economics and policy; biofuel production processes - advances and limitations; nanotechnology and its energy applications; nanotechnology in biohydrogen production - for cellulases, in algal fuel, and in bioethanol/biobutanol and biodiesel production. It is a valuable resource for researchers and engineers.